Motivational Strategies for Teacher Retention in the Rural Junior High Schools in the Jirapa District of The Upper West Region of Ghana - Alhassan, Eliasu; Libanus, Susan (EBSU Journal of Social Sciences and Humanities, 2021)
Motivation propels teacher retention in rural areas of Ghana according to Education for All Global Monitoring Report 2015. The paper examines how motivational strategies retain teachers in the rural JHSs in the Jirapa district of the Upper West Region of Ghana. Maslow's Hierarchy of Needs theory and Alderfer's ERG theory anchored this study. Cross-sectional design, Simple random, cluster and purposive sampling were used to select the 142 respondents at different levels and questionnaires were used to collect the quantitative data whilst semi-structured interview schedules and interview guide were used for the qualitative data. The quantitative data were analyzed with the help of Statistical Package for Social Sciences (SPSS) and presented in frequencies and percentages whilst the qualitative data were used to support the quantitative data in many cases. The study found that recruitment of rural teachers from rural areas to teach in the rural areas in the district does not retain teachers in rural areas. It is therefore a weak strategy, whilst enhancement in study leave and sponsorship programmes, enhancement of teachers' accommodation and improvement in social amenities in rural areas were effective strategies by which teachers are retained in the rural areas in the Jirapa District. Contrary, the study further found that poor training of teachers and lack of promotion opportunities for teachers, poor and inadequate accommodation and poor social amenities in rural areas affected teacher motivation which made many teachers lived outside the communities they teach and commuted 5-7 and more kilometers daily to teach in their respective schools. Notwithstanding, the study revealed that motivation enhanced teacher attraction and retention, improved performance and reduced teachers' absenteeism. Inadequate funds, corruption and politicization of posting of professional teacher were identified as teacher motivational challenges. It can, therefore, be said that, lack of targeting, enforcement and adequate motivation for the rural teachers perpetuated the teacher retention challenges requiring government to target, enforce and provide adequate motivational policies to retain trained teachers in rural JHSs in the Jirapa district of the Upper West Region of Ghana.